Privacy Protective Research: Facilitating Ethically Responsible Access to Administrative Data - GOROFF, DANIEL; POLONETSKY, JULES; TENE, OMER (The Annals of the American Academy of Political and Social Science, 2018)
Companies and government entities collect substantial amounts of administrative data through the Internet; mobile communications; and a vast infrastructure of devices and sensors embedded in healthcare facilities, retail outlets, public transportation, social networks, workplaces, and homes. They use administrative data to test new products and services, improve existing offerings, conduct research, and foster innovation. However, the lack of a clear legal framework and ethical guidelines for use of administrative data jeopardizes the value of important research. Concerns over legal impediments and ethical restrictions threaten to diminish productive collaboration between researchers and private sector businesses. This article provides strategies for organizations to minimize risks of reidentification and privacy violations for individual data subjects. In addition, it suggests that privacy and ethical concerns would best be managed by supporting the development of administrative data centers to lower transaction costs and increase the reproducibility of research conducted on administrative data.